2016
DOI: 10.3390/w8070297
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Linear Models to Identify Key Hydromorphological and Chemical Variables Determining the Occurrence of Macroinvertebrates in the Guayas River Basin (Ecuador)

Abstract: Abstract:The biotic integrity of the Guayas River basin in Ecuador is at environmental risk due to extensive anthropogenic activities. We investigated the potential impacts of hydromorphological and chemical variables on biotic integrity using macroinvertebrate-based bioassessments. The bioassessment methods utilized included the Biological Monitoring Working Party adapted for Colombia (BMWP-Col) and the average score per taxon (ASPT), via an extensive sampling campaign that was completed throughout the river … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 67 publications
1
28
0
1
Order By: Relevance
“…GLMs have the advantage of directly establishing and reporting the relative importance of each variable in searching for the biotic integrity [68]. Furthermore, a stepwise discriminant procedure to select the most significant variables based on the AIC selection criteria applied in this research, has been shown to be effective in the prediction of species distribution [69].…”
Section: Model Performancementioning
confidence: 97%
“…GLMs have the advantage of directly establishing and reporting the relative importance of each variable in searching for the biotic integrity [68]. Furthermore, a stepwise discriminant procedure to select the most significant variables based on the AIC selection criteria applied in this research, has been shown to be effective in the prediction of species distribution [69].…”
Section: Model Performancementioning
confidence: 97%
“…An example of this is the Guayas River basin in Ecuador wherein key ecosystems are at risk due to an increased application of pesticides. The current intensification of the human activities within the basin (agriculture, fishery, hydropower and industry) is a severe threat to the aquatic ecosystem and causes the impairment of many important ecosystem services, including habitat provision (affecting biodiversity), water provision and the safety of potable water [4][5][6]. Moreover, the changes in tillage practices negatively affected pesticide adsorption and have caused an increasing degradation of soils.…”
Section: Introductionmentioning
confidence: 99%
“…Linear statistical models have also been continuously applied as benchmarks for comparison with other statistical methods and machine learning approaches. For macroinvertebrate communities, traditional regression models are still used to relate abiotic stressors with species occurrence in order to explore habitat and water quality preferences, especially in headwaters (Pond, Krock, Cruz, & Ettema, 2017) and tropical regions (Damanik-Ambarita et al, 2016;Everaert et al, 2014;Jerves-Cobo et al, 2017). However, prediction of the biological condition under different spatial and temporal domains and scales have been also addressed in some studies for both macroinvertebrate and fish assemblages (Frimpong, Sutton, Engel, & Simon, 2005;Johnson & Host, 2010;Van Sickle & Burch Johnson, 2008).…”
Section: Linear Statistical Methodsmentioning
confidence: 99%
“…• Low predictive power • Model structure (distributions selection) must be defined a priori Low Low Damanik-Ambarita et al, 2016;Death et al, 2015;Donohue et al, 2006;Everaert et al, 2014;Gieswein et al, 2017;Holguin-Gonzalez, Everaert, et al, 2013;Jerves-Cobo et al, 2017;Kuemmerlen et al, 2014;Moya et al, 2011;Pont et al, 2009;Sauer, Domisch, Nowak, & Haase, 2011;Van Sickle et al, 2004Fukuda et al, 2013Gieswein et al, 2017;Grenouillet et al, 2011;Hermoso, Linke, Prenda, & Possingham, 2011;Kwon, Bae, Hwang, Kim, & Park, 2015;Leclere et al, 2011;Patrick & Yuan, 2017;Sui et al, 2014 Generalized additive models • Suitable for modelling nonlinear relationships • Uses nonparametric basis functions • Prone t...…”
Section: Knowledge Gap Analysismentioning
confidence: 99%